The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00280-018-3594-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of M2 macrophage markers YKL-39 and CCL18 in breast cancer is associated with the effect of neoadjuvant chemotherapy

Abstract: Thus, we showed that in patients with breast cancer who received anthracycline-containing NAC the absence of clinical response is associated with the presence of M2+ macrophage phenotype (YKL-39-CCL18 + or YKL-39 + CCL18-) based on TOP2a overexpression data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…We found that high gene expression of YKL-39, in biopsies obtained before NAC, positively correlated with increased risk of distant metastasis and poor response (stabilization or progressive disease) to therapy (17) ( Table 7). In our other study that included 68 female patients with BC (Russian cohort) who received anthracycline-containing NAC, the absence of clinical response is associated with the presence of M2+ macrophage phenotype (YKL-39-CCL18+ or YKL-39+CCL18−) (20). In our study of patients who underwent neoadjuvant chemotherapy (multiple schemes) CD68+ TAMs in areas with parenchymal elements negatively correlated with lymphatic metastasis (52).…”
Section: Tams and Breast Cancer Treatmentmentioning
confidence: 68%
See 1 more Smart Citation
“…We found that high gene expression of YKL-39, in biopsies obtained before NAC, positively correlated with increased risk of distant metastasis and poor response (stabilization or progressive disease) to therapy (17) ( Table 7). In our other study that included 68 female patients with BC (Russian cohort) who received anthracycline-containing NAC, the absence of clinical response is associated with the presence of M2+ macrophage phenotype (YKL-39-CCL18+ or YKL-39+CCL18−) (20). In our study of patients who underwent neoadjuvant chemotherapy (multiple schemes) CD68+ TAMs in areas with parenchymal elements negatively correlated with lymphatic metastasis (52).…”
Section: Tams and Breast Cancer Treatmentmentioning
confidence: 68%
“…In addition to scavenging function (10,11,13), stabilin-1 acts as an intracellular sorting receptor that targets chitinase-like proteins SI-CLP and YKL-39 to the secretory pathway (14)(15)(16)(17)(18)(19). SI-CLP and YKL-39, in turn, regulate monocyte recruitment and angiogenesis (15,17,18,20).…”
Section: Introductionmentioning
confidence: 99%
“…12 CCL18, a member of the CC chemokine family, is mainly secreted by M2-type TAMs. 7,8 Excessive secretion of CCL18 has been observed in multiple human malignancies, including breast carcinoma, [9][10][11]13 hepatocellular carcinoma, 14 ovarian cancer, 15,16 nasopharyngeal carcinoma, 17 lung cancer, [18][19][20] colon cancer 21,22 and pancreatic ductal adenocarcinoma. 23,24 Expression of CCL18 is associated with tumour initiation and progression, and therefore, could be used to predict the prognosis of patients with breast cancer.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Tumor-associated macrophage is an essential factor affecting the efficiency of chemotherapy. Among the breast cancer patients with TOP2A overexpression, the absence of clinical response to anthracycline-containing neoadjuvant chemotherapy is associated with the presence of M2+ macrophage phenotype ( Litviakov et al, 2018 ). In addition, TOP2A expression level was significantly negatively correlated with the numbers of macrophages in gastric cancer tissues ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%